Harmonisasi Hukum Pemilu dan Hukum Siber dalam Pengaturan Kampanye Hitam di Ruang Digital: Kajian Normatif Yuridis: Harmonization of Electoral Law and Cyber Law in Regulating Black Campaigns in the Digital Sphere: A Normative Juridical Study - Ramdhani Pasya, Bayu Rosa; Rahim, Erman; Mandjo, Julius T (Information Technology and Science (ITScience), 2026)
The phenomenon of black campaigns in the digital sphere has emerged as a new challenge in safeguarding the integrity of elections in Indonesia. The rapid development of information technology has made the dissemination of hate speech and negative campaigning increasingly difficult to control, while the existing legal framework has not yet become fully responsive to these developments. This study is motivated by the normative disharmony between Article 280 paragraph (1) of Law Number 7 of 2017 on General Elections and Article 28 paragraph (2) of Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law), both of which are relevant to the regulation of political campaign behavior in digital spaces. The objective of this research is to analyze the relevance, interrelationship, and effectiveness of these two provisions in shaping a coherent legal normative system governing black campaigns. The research employs a normative legal research method with statutory, interpretative, and conceptual approaches. Data are collected through library research, encompassing statutory regulations, legal literature, and official documents issued by electoral management bodies. Data analysis is conducted qualitatively through grammatical, systematic, and teleological interpretation in order to assess the harmony of legal norms and their implications for legal practice in the field. The findings indicate that there is a disharmony between the two legal norms. The Election Law functions as lex specialis but has a limited scope in terms of legal subjects, whereas the ITE Law operates as lex generalis with broader applicability. This normative inconsistency generates legal ambiguity and creates challenges in law enforcement against perpetrators of digital black campaigns. In conclusion, harmonization and normative integration between the Election Law and the ITE Law are necessary to ensure that Indonesia’s digital electoral legal system becomes more adaptive, clear, and effective in addressing black campaign practices while upholding justice and ethical standards in digital democracy.